IMPLEMENTASI PERATURAN WALIKOTA SURABAYA NOMOR 25 TAHUN 2016 TENTANG TATA CARA PEMBERIAN DAN PERTANGGUNGJAWABAN HIBAH DAN BANTUAN SOSIAL - Idrus . (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
The method used in this research is qualitative research method (qualitative research). Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, perceptual beliefs, thoughts of individuals individually or in groups. The population in this study consisted of: 1) Head of Surabaya City Social Service, 2) Head of Surabaya City Social Service UPTD, 3) Implementer, 4) Beneficiary. The sampling technique used "purposive" with the selection criteria for this information based on subjects who mastered the problem and were willing to provide data. So that informants were obtained: 1) Head of Surabaya City Social Service: Drs. Supomo, MM., 2) Head of UPTD Surabaya Social Service Office , 3) Executor: Kuncoro Chairperson of RW 1, 4) Beneficiaries: Lusi Chairperson of Al Qomariyah Study, the research found that the implementation of Surabaya mayor regulation number 25 of 2016 concerning the procedures for granting and accounting for grants and social assistance is intended to relieve community members who are not able and neglected so that they can still meet their basic living needs (Basic Living Needs) and develop themselves as human beings in accordance with humanity with dignity as the implementation of constitutional mandates for the central and or regional governments. The implementation is not in accordance with applicable regulations, so that there arises phenomena the researcher do not observe about the distribution of grants and social assistance, among others: Dissemination of program less than optimal, Implementation of social assistance programs and grants using invalid recipient social assistance / grant data, many beneficiaries did not carry out data verification, implementation of beneficiaries was considered to be very poor, there are rejections or protests from various elements of society, there is still overlap in the distribution of social assistance / grants, social assistance funds to educate corrupt communities and nepotism. Factors that influence the implementation of Surabaya mayor regulation number 25 of 2016 include communication, resources, disposition and bureaucratic structure.